Strategi PT Indofood dalam Memasuki Pasar Nigeria Tahun 2024-2025 - Iis Mulyani; Lita Sari Rahayu; Muhammad Rizki Al-Fataah; Zalif Nasrudin; Septianis Afipah (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study discusses PT Indofood's strategy in expanding its market penetration in Nigeria during 2024-2025, emphasizing the influence of the country's political structure and regulations on the dynamics of corporate expansion. Nigeria is a potential market with a large population, but political instability, fluctuations in import policies, and government intervention in the food sector create significant obstacles for multinational companies. The research uses a qualitative-descriptive approach through a single case study of Indofood and its joint venture, Dufil Prima Foods, utilizing secondary data from official reports, academic publications, and credible business reports to strengthen the validity of the findings. The results of the discussion show that fluctuating political stability and exchange rate liberalization policies affect Indofood's production costs, supply chain strategies, and marketing adaptation patterns. The company applies its advantages as an EMNC through cost efficiency, localization of raw materials, and value chain resilience to respond to political and economic risks. This study confirms that Indofood's success in Nigeria is highly dependent on its ability to read political dynamics and design adaptive strategies to changes in state policy.